STUDENT'S VIEW TOWARDS THE USE OF GOOGLE FORM APPLICATION IN TEACHING READING - I putri Enggo Untari (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
As the progressive development of the Information and Communication Technology (ICT) in 21st century affects teaching and learning process, it help the teacher and student to make teaching learning activity easy and interesting. Moreover, with the correct and proper online education, for example by Google Form quizzes, the students are encourage to gather the information from multiple resources within the internet and free access for anytime and anywhere. This research aimed to know the students’ experience and the quality using Google form during online learning which conducted at eighth grade of junior high school in Sragen with 32 students as the sample and the data were collected by observing, interviewing, documenting, and distributing questionnaires. This research used qualitative method which shows that 57% of the students agree about the benefits of using Google forms to facilitate reading learning. As many as 32% of students expressed neutral, 4% expressed disagree, 4% stated strongly disagree, and 3% stated strongly agree about benefits of using Google forms. Thus, it can be concluded that the use of Google Forms in improving reading skill which it facilitate reading learning, most of the students felt easy and can gain benefits from using Google Form in studying reading. Keywords: Information and Communication Technology (ICT), online learning, Google Form Application, Reading Skill